1994
DOI: 10.2307/146254
|View full text |Cite
|
Sign up to set email alerts
|

Turnover and Promotion of Lawyers: An Inquiry into Gender Differences

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. University of Wisconsin Press andThe Board of Regents of the University of Wisconsin System are collaborating with JSTOR to digitize, preserve and extend access to The Journal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 43 publications
1
26
0
1
Order By: Relevance
“…Several previous studies have found that women's prospects of promotion to law firm partnership are lower than men's (Spurr 1990;Spurr and Sueyoshi 1994;Hagan 1998, 1999;Gorman 2006). In this study, in line with the contrast between entry and "top" levels implicit in the glass ceiling metaphor (Hymowitz and Schellhardt 1986), we compare women's mobility into entering associate positions with their mobility into partner positions.…”
Section: Research Setting: Corporate Law Firmsmentioning
confidence: 80%
“…Several previous studies have found that women's prospects of promotion to law firm partnership are lower than men's (Spurr 1990;Spurr and Sueyoshi 1994;Hagan 1998, 1999;Gorman 2006). In this study, in line with the contrast between entry and "top" levels implicit in the glass ceiling metaphor (Hymowitz and Schellhardt 1986), we compare women's mobility into entering associate positions with their mobility into partner positions.…”
Section: Research Setting: Corporate Law Firmsmentioning
confidence: 80%
“…For example, Dixon and Seron (1995) found that only 8% of partners in leading law firms in the US were women in the late 1980s. Similarly, Hagan and Kay (1995), Hull and Nelson (2000), Kay (1997), Kay andHagan (1998, 1999), Noonan and Corcoran (2004), Spurr (1990), Spurr and Sueyoshi (1994) found, after controlling for productivity, academic distinction, and rank of law school work experience, marital status, current work hours and other measures of social capital, that women were less likely to achieve partnership. Spurr (1990) found that male lawyers were twice as likely to attain partnership.…”
Section: Determinants Of Partnership Attainmentmentioning
confidence: 90%
“…One example of such a position is what has been referred to as the "mommy track", which allows women to balance work and family, taking time out to raise children or work fewer hours (Crosby, 1991;Futter, 1989). However, many women who choose or are forced to follow this track find that it results in career paths that are less lucrative and less likely to lead to job advancement such as partnership in law firms (Bender, 1989;England et al, 1994;Huang, 1997;Spurr & Sueyoshi, 1994). Indeed, Elias and Shitrai (1998) found that after controlling for human capital and occupational segmentation, male lawyers in Israel still earned more that female lawyers when occupying the same job status.…”
Section: Occupational Segmentation Theorymentioning
confidence: 99%
“…Such evidence has not, however, been as consistently found in studies of other occupational groups. Of the several studies of North American lawyers, Spurr (1990) and Spurr and Sueyoshi (1994) both concluded that their ®ndings`suggested' discrimination against women but Laband and Lentz (1993) were unable to ®nd consistent evidence in relation to earnings or promotion, though they reported that women were treated less well than men. In addition, with regard to US federal employees, Lewis (1986) found no evidence of discrimination.…”
Section: Introductionmentioning
confidence: 99%
“…Building on the pioneering studies of Oaxaca (1973) and Greenhalgh (1980) , most recent work has dealt with changes in the size of the diVerential over time (Blau and Beller, 1988;Foot and Stager, 1990;Katz and Murphy, 1992;O'Neill and Polachek, 1993;Spurr and Sueyoshi, 1994;Kahn, 1995, 1997;Loury, 1997). However, the goal of this study is to examine the contribution of diVerent factors to the size of this diVerential at a point in time.…”
Section: Introductionmentioning
confidence: 99%